FENOMENA PERGESERAN FUNGSI INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PEMASARAN ONLINE (STUDI PADA AKUN @BROKEBUTCOOL_) - Zahra Shafira; Christiana Wulandari (JURNAL BADATI, 2021)
The function of Instagram, which is currently switching, makes it easier for business people to market each of their products on Instagram social media, one of business accounts that is taking advantage of this shift is @brokebutcool_. The purpose of this study is to find out how the shift in the function of Instagram and the marketing communication strategy applied to the @brokebutcool_ account. The theory used in this research is Cyber Communications Theory: Mediamorphosis, Integrated Marketing Communication which acts as an effort made by the company in informing its products to consumers, and uses the 4P model in the process of analyzing it, namely Product, Price, Place, and Promotion. This study uses a constructive paradigm with a qualitative descriptive method. The technique to collect data is literature studies, observation, and interviews. The results of this study indicate that the shift in the function of Instagram occurs because of its flexible nature, can be a place for marketing communication without the use of fees, and can be accessed globally, the marketing communication strategy applied to @brokebutcool_ is that there are some interesting content to attract customer which are, testimony, best finds, sharing some story, movies, fashion styling inspiration, give away, and tiktok inspo which are included in the highlight feature of their Instagram account. The conclusion of this study is that the shift in the function of Instagram as a marketing communication medium and business platform is not only beneficial for business people but also makes it easier for consumers to satisfy several needs without going to the shopping center or leaving the house.Â